Evaluating The Performance Of The International Investment Portfolio Of A Sample Of US Government Treasury Bonds Using The Return And Risk Model To Rationalize The Investment Decision ((An Analytical Study)) - العربيد نضال; جانم منهل (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the research is to evaluate the performance of the international investment portfolio using the return and risk model to rationalize the investment decision by making a comparison between the available investment tools and choosing the best investment alternative, depending on the appropriate methods and tools to measure performance. To achieve the objectives of the study, the researcher obtained data for 40 us government treasury bonds whose maturities ranged between one and three years, and they were divided according to priority of maturity, into four equal groups, each group of 10 bonds, then computed the difference factor for each group and measured the correlation coefficients between them, and study forming an investment portfolio consisting of two groups of these groups (diversification) that are the least connected, and arriving at the conclusion that the investment portfolio consisting of the bonds of the first and fourth groups together in equal proportions (distributing the amount allocated to the purchase of bonds between the two groups equally) is the best performance (the lowest coefficient of variation), and can improving the performance of this portfolio by increasing the relative weight of the bonds of the fourth group (the lowest coefficient of variation) by 86% of the total value of these two groups that make up the portfolio.